2014
DOI: 10.1177/0022034514557545
|View full text |Cite
|
Sign up to set email alerts
|

TLR2 Promoter Hypermethylation Creates Innate Immune Dysbiosis

Abstract: Periodontitis is a common chronic inflammatory disease that is initiated by a complex microbial biofilm that poses significant health and financial burdens globally. Porphyromonas gingivalis is a predominant pathogen that maintains chronic inflammatory periodontitis. Toll-like receptors (TLRs) play an important role in periodontitis by recognizing pathogens and maintaining tissue homeostasis. Deficiencies in TLR expression and downstream signaling may reduce the host's innate defenses against pathogens, leadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(92 citation statements)
references
References 39 publications
5
83
0
2
Order By: Relevance
“…*, P Ͻ 0.05; **, P Ͻ 0.01; ***, P Ͻ 0.001; ****, P Ͻ 0.0001. (40), whereas P. gingivalis-induced TNF production is predominantly driven by the TLR2-MyD88 pathway in macrophages (41). The latter finding may possibly explain why TLR9 deficiency had a relatively modest effect on TNF production as opposed to its effect on IL-6.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…*, P Ͻ 0.05; **, P Ͻ 0.01; ***, P Ͻ 0.001; ****, P Ͻ 0.0001. (40), whereas P. gingivalis-induced TNF production is predominantly driven by the TLR2-MyD88 pathway in macrophages (41). The latter finding may possibly explain why TLR9 deficiency had a relatively modest effect on TNF production as opposed to its effect on IL-6.…”
Section: Discussionmentioning
confidence: 95%
“…Disruption of this homeostatic balance by certain environmental exposures (e.g., smoking, obesity, or stress), host genetic and epigenetic defects in innate responses, or subversion of the host response by dysbiotic microflora can lead to destructive inflammation, precipitating periodontitis (35)(36)(37)(38)(39)(40)(41). Recently, TLR9 signaling has emerged as a potential inflammatory pathway in periodontitis pathogenesis on the basis of clinical and in vitro investigations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements were expressed in square millimeters by converting pixels to millimeters. For the hematoxylin and eosin (H&E) coronal section, the length between the CEJ to the alveolar ridge has been measured as described previously 20 …”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have also shown increased methylation of CpG sites in the promoter region of the gene and a resulting decrease in tlr2 expression, which has been implicated in the development of the condition 24 . Hypermethylation of tlr2 has also been implicated in dysbiosis of the innate immune system as a whole, with studies linking aberrant methylation of the gene to decreased global innate immune response and susceptibility to disease 25 …”
Section: Toll‐like Receptors and Diseasementioning
confidence: 99%